Analyzing Early Feedback: Survey Findings from Elementary Teacher Candidates for AI Comic Development Training Workshop - Ibrahim Ibrahim; Muhammad Syazali; Gita Prima Putra (JURNAL PENDIDIKAN MIPA, 2024)
This research aims to investigateinterest and readiness of prospective elementary school (SD) teachers towards training workshopscomic-based developmentArtificial Intelligence (AI). Through surveysof 104 respondents, data was collected and analyzed to evaluatethe level of interest, obstacles faced, and the urgency of such training.The results show that the majority of respondents (49%) expressed readinessto take part in the workshop, while 48.1% gave the answer "maybewilling". However, 2.9% of respondents showed disagreement withthe workshop. The main obstacle identified was difficulty indrawing characters (76.9%) and writing story scripts (30.8%). Urgency fororganizing such workshops lies in the potential to improveprospective elementary school teachers' skills in using new technology to supportlearning, while creating an innovative and learning environmentrelevant for students in this digital era. Thus, this researchprovides valuable insights for workshop organizers and educatorsin designing training programs that suit the needs and interests of candidateselementary school teachers in developing comics with artificial intelligence technology.